Generations of chaos-modulated pulses based on a gain-switched semiconductor laser subject to delay-synchronized optical feedback for pulsed chaos lidar applications - Tsay, Han-Ling; Wang, Chong-Yu; Chen, Jun-Da; Lin, Fan-Yi (Optics express, 2020)
We generate and analyze chaos-modulated pulses based on a gain-switched semiconductor laser subject to delay-synchronized optical feedback for pulsed chaos lidar applications. Benefited by the aperiodic and uncorrelated chaos waveforms, chaos lidar possesses the advantages of no range ambiguity and immunity to interference and jamming. To improve the detection range while in compliance with the eye-safe regulation, generating chaos-modulated pulses with higher peak power rather than chaos in its CW form is desired. While using an acousto-optic modulator to time-gate the CW chaos into pulses could be lossy and energy inefficient, in this paper, we study the generation of chaos-modulated pulses using a gain-switched laser subject to delay-synchronized optical feedback. Under different feedback strengths and modulation currents of gain-switching, we investigate the quality of the chaos-modulated pulses generated by analyzing their ratio of chaos oscillations, peak sidelobe levels (PSLs), and cross-correlation peaks under different mismatching conditions between the pulse repetition interval (PRI) and the feedback time delay τ . With proper feedback strengths and modulation currents, we find that synchronizing the gain-switching modulation with the delayed feedback (PRI = τ ) is essential in generating the chaos-modulated pulses suitable for the pulsed chaos lidar applications. When mismatching occurs, we identify sequences of dynamical periods including stable, periodic, and chaos oscillations evolved within a pulse.